A Comparison of Schools of Law in Philosophy: Natural Law, Positive Law, and Modern Schools - Ilmiati Ilmiati; Muhammad Mutawalli (Publikasi Indonesia, 2024)
The philosophy of law is a branch of science that combines philosophy and law. Philosophy uses rational reason as its concept and system, and law uses evidence as its tool and concept. Throughout its history, philosophy has come up with various methods and concepts in presenting new scientific discoveries that are beneficial to humans. Philosophical schools are a method as well as a medium for philosophy to display its development from time to time. By combining an inquisitive mentality and a critical rational mind, philosophy is a complex branch of science. Starting from the habits of human life, and the secrets of the universe to the relationship between God, humans, and nature. Because of its completeness in presenting new knowledge and knowledge, philosophy and its schools cannot be separated from one another to witness the history of the development of philosophy itself. The philosophy of law, that is, philosophy and law have much in common. One of the similarities between the two is that they both use rational reason and concrete evidence as their media so famous philosophers juxtapose the two to declare the existence of each so that it is more complete and acceptable to the next human being.